Habitat fragmentation: Simple models for local persistence and the spread of invasive species - Brown, R.G.; James, A.F.; Pitchford, J.W.; Plank, M.J. (Journal of theoretical biology, 2012)
Understanding the persistence and growth of natural populations in environments subject to random localised change is relevant both to the conservation of threatened species and to the control of invasive species. By developing and analysing simple strategic growth models in environments subject to random fragmentation events, we show that simple approximations can be used to predict invasion speeds and extinction probabilities. The rate and size of fragmentation events interact in a nonlinear way, a finding with important consequences for the efficient control of invasive species. Infrequent, large-scale fragmentation events provide more effective means of control than more frequent, smaller scale efforts. ► Population spread speed and persistence in a randomly fragmented environment. ► Continuum limit of stochastic process allows analytical insight into spatial phenomena. ► Implications for control of invasive species.